Tujuan Pendidikan dalam Perspektif Al-Quran - Hidayatullah (LP2M Universitas PTIQ Jakarta, 2016)
This article discusses the purpose of Education in the Qur’anic Perspective, which focused on optimization the goal of education and learning for the complete devotion according to Allah’s command and the guidance given by the Prophet. The optimization of educational and learning facilities is done in ways that are appropriate to educate Rasul SAW., on his companions, resulting in a form of religious education, environmentally friendly, appreciation of achievement, weak protection and mutual cooperation in religious, social and community life. The purpose of education in the Qur’an is to form the whole Muslim individual, to develop all human potentials both physically and spiritually, to cultivate the harmonious relationship of every person with God, and to establish good communication with fellow humans and the universe.